Thyroid hormone and mitochondrial biogenesis - Weitzel, Joachim (Henry Stewart Talks, 2007)
Synthesis of thyroid hormone (TH), Local bioavailability, Conversion of thyroxine by deiodination, TH and gene expression, Molecular readout of TH, TH and chromatin structure, Non-genomic effects of TH, Extra-cellular binding to integrins, TH metabolism, TH derivatives, TH derivatives and their impact on mitochondrial biogenesis, Thyronamines
Reviewed at 2022/04/12